Translating regenerative medicine to the clinic - Laurence, Jeffrey; Baptista, Pedro; Atala, Anthony, 1958-; Beusekom, Mary van (London : Academic Press, 2015)
This review of current methodological tools and experimental approaches used by leading translational researchers, discusses the uses of regenerative medicine for different disease treatment areas, including cardiovascular disease, muscle regeneration and regeneration of the bone and skin. Pedagogically, it concentrates on the latest knowledge, laboratory techniques and experimental approaches used by research leaders in the field. It promotes cross-disciplinary communication between the sub-specialties of medicine, but remains unified in theme by emphasising recent innovations, critical barriers to progress, the new tools that are being used to overcome them and specific areas of research that require additional study to advance the field as a whole.
3.1.1 Endothelial Progenitor Cells and MSCs3.1.2 Embryonic and Inducible Stem Cells; 3.1.3 BM Cells; 3.1.4 Cell Seeding Techniques; 3.2 Implants as an In Situ'Cell-Free' Tissue Forming Device; 3.3 Implants as a Drug Delivery Vehicle; 4. CLINICAL APPLICATIONS IN CARDIOVASCULAR REPAIR; 4.1 Vascular; 4.1.1 Vascular Patch; 4.1.2 Vascular Grafts; 4.2 Heart Valve; 4.3 Heart; 5. CONCLUSION; ACKNOWLEDGMENT; REFERENCES; 5 -- Tissue Engineering and Regenerative Medicine: Gastrointestinal Application; Key Concepts; 1. THE GASTROINTESTINAL TRACT: OVERVIEW; 2. NEURODEGENERATIVE DISEASES OF THE GI TRACT
Academic Press is an imprint of Elsevier
Includes index.
Online resource; title from title details screen (ScienceDirect, viewed December 2, 2015).
Elsevier
Keywords: Regenerative Medicine; Clinical medicine; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; Clinical medicine; Regenerative medicine; Electronic books; Electronic books